2016
DOI: 10.4137/cmc.s35734
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Patients with Non-ST Segment Elevation Myocardial Infarction using Strain Doppler Echocardiography: Correlation with Cardiac Magnetic Resonance Imaging

Abstract: Assessment of left ventricular (LV) function is important for decision-making and risk stratification in patients with acute coronary syndrome. Many patients with non-ST segment elevation myocardial infarction (NSTEMI) have substantial infarction, but these patients often do not reveal clinical signs of instability, and they rarely fulfill criteria for acute revascularization therapy.AIMThis study evaluated the potential of strain Doppler echocardiography analysis for the assessment of LV infarct size when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…21 In a study they found negative correlation of LVEF and troponin-I levels in Acute MI patients, strength of association was r = -0.269. 22 All these findings are consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…21 In a study they found negative correlation of LVEF and troponin-I levels in Acute MI patients, strength of association was r = -0.269. 22 All these findings are consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%